Triple Antiphospholipid (aPL) Antibodies Positivity Is Associated With Pregnancy Complications in aPL Carriers: A Multicenter Study on 62 Pregnancies - Lazzaroni, Maria-Grazia; Fredi, Micaela; Andreoli, Laura; Chighizola, Cecilia Beatrice; Del Ross, Teresa; Gerosa, Maria; Kuzenko, Anna; Raimondo, Maria-Gabriella; Lojacono, Andrea; Ramazzotto, Francesca; Zatti, Sonia; Trespidi, Laura; et al. (Frontiers in Immunology, 2019)
Objective: Antiphospholipid antibodies (aPL) are risk factors for thrombosis and adverse obstetric outcomes. The pregnancy outcome and the treatment of the so called “aPL carriers” patients (aPL positivity without the clinical manifestations of APS) are still unclear. This study aims at retrospectively evaluate the outcome and the factors associated with complications in 62 aPL carriers pregnant women. Methods: Medical records of pregnant women regularly attending 3 Rheumatology centres with a Pregnancy Clinic from January 1994 to December 2015 were retrospectively evaluated. Patients with concomitant autoimmune diseases or other causes of pregnancy complications were excluded. Results: An aPL-related complication was recorded in 8 out of 62 patients during pregnancy (12.9%): 2 thrombosis and 6 adverse pregnancy outcomes (APO). At the univariate analysis, factors associated with pregnancy complications were acquired risk factors (p:0.008), non-criteria aPL manifestations (p:0.024), lupus-like manifestations (p:0.013) and triple positive aPL profile (p:0.001). At the multivariate analysis, only the association with a triple aPL profile was confirmed (p:0.01, OR 21.3, CI 95% 1.84-247). Patients with triple aPL positivity had an increased rate of pregnancy complications, while more frequently receiving the most intensive treatment of low dose aspirin (LDA) combined with low molecular weight heparin (LMWH). Conclusion: This study highlights the importance to define a risk profile for aPL carriers pregnant women, in term of immunologic and non-immunologic features. Combination treatment with LDA and LMWH seems to be insufficient to prevent APO in some cases, especially in patients with triple aPL positivity, that could deserve additional therapeutic strategies.